Comparison of endoscopic spine surgery and minimally invasive transforaminal lumbar interbody fusion for degenerative lumbar disease: A meta-analysis. (June 2021) - Sik Goh, Tae; Hwan Park, Shi; Suk Kim, Dong; Ryu, Seungyoon; Min Son, Seung; Sub Lee, Jung
Abstract: This study aimed to compare the clinical outcomes of endoscopic spinal surgery (ESS) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) for degenerative lumbar disease (DLD) through meta -analysis. The Medline (via PubMed), Cochrane, Scopus, and Embase databases were searched for studies that evaluated the outcomes of ESS and MIS-TLIF in DLD, including visual analog scale (VAS) score for low back pain, VAS score for leg pain, Oswestry Disability Index (ODI), and complications published between January 2000 and August 2020. Two authors extracted the data independently. Any discrepancies were resolved by a consensus. Four comparative studies were identified. No significant differences were found between the ESS and MIS-TLIF groups in terms of VAS score for back pain, VAS score for leg pain, and ODI, except for complication rate. The complication rate was higher in the ESS than in the MIS-TLIF group. A literature review identified four comparative studies reporting the clinical outcomes of ESS and MIS-TLIF for DLD. Despite the heterogeneity, a limited number of meta -analyses showed that the clinical outcomes between the two groups were not significantly different except for complication rate. Hence, further large-scale multicenter studies are required to validate our results.